2015
DOI: 10.1016/j.cub.2015.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Human infants’ ability to perceive touch in external space develops postnatally

Abstract: Arriving in the outside world, the newborn infant has to determine how the tactile stimulation experienced in utero relates to the spatial environment newly offered up by vision, hearing and olfaction. We investigated this developmental process by tracing the origins of the influence of external spatial representation on young infants' orienting responses to tactile stimuli. When adults cross their hands or feet they typically make more tactile localization errors than otherwise, and this has been attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 10 publications
11
60
0
Order By: Relevance
“…The normal development of functions not directly related to vision may require larger amounts of experience and therefore longer periods of visual input (Wallace & Stein, ). Indeed, recent reports have shown that significant postnatal experience is required to remap touch automatically in external space (Begum Ali et al., ; Bremner, Mareschal, et al., ; Rigato et al., ). Bremner, Mareschal, et al.…”
Section: Discussionmentioning
confidence: 99%
“…The normal development of functions not directly related to vision may require larger amounts of experience and therefore longer periods of visual input (Wallace & Stein, ). Indeed, recent reports have shown that significant postnatal experience is required to remap touch automatically in external space (Begum Ali et al., ; Bremner, Mareschal, et al., ; Rigato et al., ). Bremner, Mareschal, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bremner, Mareschal, Lloyd‐Fox, and Spence () looked at infants’ first correct unilateral hand movement and orienting responses to hand stimulation in a crossed posture and observed that at 10 months, infants’ responses were modulated by the posture, whereas 6‐month‐olds performed equivalently. In a later study, responses to stimuli at crossed feet were modulated in 6‐month‐olds, but not in 4‐month‐old infants (Begum Ali et al ., ). The authors interpreted these results as indicating that the use of external or spatial information localizing touch develops between 4 and 6 months.…”
Section: Introductionmentioning
confidence: 97%
“…() and Begum Ali et al . (). We expected infants to demonstrate functional knowledge about the body's configuration by producing specific orienting responses or movement and activity patterns associated with the stimulated body area (Watanabe & Taga, , ).…”
Section: Introductionmentioning
confidence: 97%
“…They found that at 3 months infants responded with global movements of their body and, at 5–6 months, infants responded more specifically with the hand or foot stimulated by the buzzer. Other studies showed that already at the earliest ages tested (6 months for the hands and 4 months for the feet) infants can locate an unseen vibrotactile stimulus on the hands (Bremner, Mareschal, Lloyd‐Fox, & Spence, ) and on the feet (Begum Ali, Bremner & Spence, ). In these studies, infants showed more manual and visual orientation towards the stimulated limb compared with the non‐stimulated limb.…”
Section: Introductionmentioning
confidence: 99%